Muslim pertama : melihat Muhammad lebih dekat / Lesley Hazleton ; penerjemah, Adi Toha ; editor, Indi Aunullah - HAZLETON, Lesley; Adi Toha; Indi Aunullah (Pustaka Alvabet, 2013)
372 hlm. 23 cm. (3 eks.)